1996
DOI: 10.1021/bi952334k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Escherichia coli UDP-N-Acetylmuramate:l-Alanine Ligase

Abstract: Uridine diphosphate N-acetylmuramate:L-alanine ligase (EC 6.3.2.8, UNAM:L-Ala ligase or MurC gene product) adds the first amino acid to the sugar moiety of the peptidoglycan precursor, catalyzing one of the essential steps in cell wall biosynthesis for both gram-positive and gram-negative bacteria. Here, we report our studies on the secondary and quaternary structures of UNAM:L-Ala ligase from Escherichia coli. The molecular weight of the purified recombinant enzyme determined by electrospray ionization mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
3
32
0
1
Order By: Relevance
“…The UDP-MurNAc:L-Ala and UDP-MurNAc:Gly ligase activities were assayed as described by Liger et al (12). For this purpose, UDP-MurNAc was prepared by a two-step coupled enzymatic conversion of UDP-GlcNAc to UDP-MurNAc according to Jin et al (9) and identified through negative-ion fast atom bombardment-mass spectroscopy (FAB-MS) (the expected mass of 679 was observed) and nuclear magnetic resonance (NMR) (300 MHz). The following signals were clearly identified by 1 acid-1 M ammonium hydroxide (5:3) to separate the reaction product from unreacted amino acids.…”
mentioning
confidence: 99%
“…The UDP-MurNAc:L-Ala and UDP-MurNAc:Gly ligase activities were assayed as described by Liger et al (12). For this purpose, UDP-MurNAc was prepared by a two-step coupled enzymatic conversion of UDP-GlcNAc to UDP-MurNAc according to Jin et al (9) and identified through negative-ion fast atom bombardment-mass spectroscopy (FAB-MS) (the expected mass of 679 was observed) and nuclear magnetic resonance (NMR) (300 MHz). The following signals were clearly identified by 1 acid-1 M ammonium hydroxide (5:3) to separate the reaction product from unreacted amino acids.…”
mentioning
confidence: 99%
“…Interestingly, Ec MurC (PDB 2f00) is also a dimer in the crystal structure but, in solution, displays a dynamic equilibrium between monomeric and dimeric forms. Both forms were shown to be active [16], [60]. The PFYG (residues 222–225) motif in Ec MurC (corresponding to PSTG, residues 232–235, in Pa Mpl), which is conserved in ∼50% of MurC proteins, is involved in dimerization.…”
Section: Resultsmentioning
confidence: 99%
“…The dimer interface is formed by the interaction of loops from the top of domain II of one molecule with loops from domain I of the second molecule and the most important interactions involve Phe223 and Tyr224 [83], however in M. tuberculosis the corresponding residues are not conserved (Pro218 and Gly219).…”
Section: Methodsmentioning
confidence: 99%